Interleukin 1 beta, hand and foot bone mineral content and the development of joint erosions in rheumatoid arthritis. Issue 8 (August 1994) - North, J; Situnayake, R D; Tikly, M; Cremona, A; Nicoll, J; Kumararatne, D S; Nuki, G
Abstract : OBJECTIVE--To assess the relationship between plasma levels of the cytokine interleukin-1 beta (IL-1 beta) and the progression of rheumatoid arthritis (RA). METHODS--Two subgroups of patients, one with persistently raised ESR (>/= 50 mm/hour, n = 16, group A) and one with persistently low ESR (</= 28 mm/hour), n = 18, group I) were chosen to represent stable extremes of inflammatory activity from a prospective study of 106 patients with active RA studied over one year in a single centre. The change from baseline in hand, foot and calcaneal bone mineral content measured by single photon absorptiometry and radiographic score of joint damage was measured over 12 months, together with plasma IL-1 beta and erythrocyte sedimentation rate. RESULTS--Significant progression of joint damage occurred in both subgroups over one year (p < 0.0001, paired t test) though progression was significantly less in the subgroup with low ESR (p < 0.05, ANOVA). Hand and foot bone mineral content decreased by almost 10% in the subgroup with raised ESR (p < 0.005, paired t test). Stepwise linear regression analysis revealed significant independent relationships between radiographic progression over one year and plasma IL-1 beta and ESR (multiple R 0.674, F = 11.64, p < 0.0002). No such relationships were observed for changes in bone mineral content parameters. CONCLUSIONS--Plasma IL-1 beta levels correlate weakly with progression of joint damage though not with loss of peripheral bone density in RA. A significant reduction in peripheral bone mineral content occurs over one year in patients with active RA with persistently raised ESR.